(untitled) (Orfeu, 2025)
This article analyses data from the research What do I Want from Music?: Musical Studies Among Adults with Other Professional Occupations, which investigated the motivations and experiences of students aged 35 or older, engaged in other professions, who were enrolled in music lessons at four educational institutions in João Pessoa –PB. Using the Musical Life History approach, data was collected through autobiographical narrative interviews. Through qualitative analysis, the study revealed meaningful musical experiences during childhood and adolescence –often occurring in informal and non-formal educational settings –that contributed to embodied cultural capital. In early adulthood, professional and family obligations often led to a distancing from musicalactivities. Taking up music lessons again during a more flexible phase of life resulted in reports of pleasure, well-being and personal fulfilment, as well as the rediscovery of postponed personal aspirations. Thus, music became both a leisure activity and a practice of lifelong learning.